Proses Kerja Komputer yang dapat Mengoptimalkan Hasil Komunikasi Visual secara Efisien - Darmawan, Andreas James (Humaniora, 2010)
To be able to work optimally and efficiently by computer, in making a visual communication, we need to understand the three kinds of process/ how to work a computer. There are three bases logic how computer works, such as text, pixel, and vector. Each made with different methods of logic, as a result of efforts to meet the needs of creators of computer communication. So after the third understands the workings of TSB, the ease and optimization in making a visual communication can be achieved.